Assessing the Effects of Environmental Enrichment on Behavioural Deficits in C57BL Mice. Issue 2 (May 2014) - Coombs, Ellen J.
A study on the effects of environmental enrichment on behaviour and cognitive and motor functioning in a standard mouse model and a strain known to have behavioural deficits, suggests that environmental enrichment can positively influence natural functioning and natural behaviour